GAMBARAN TINGKAT KECEMASAN PADA ANAK KANKER SEBELUM MENJALANI KEMOTERAPI DI RUMAH SINGGAH YAYASAN PEDULI KANKER ANAK BALI - Putri, Putu Aristya; Kadek, Cahya Utami; Juniartha, I Gusti Ngurah (Coping: Community of Publishing in Nursing; Vol 8 No 3 (2020): Oktober 2020DO - 10.24843/coping.2020.v08.i03.p04, 2020)
Cancer is an abnormal cells, growing progressively, unable to function physiologically which can threaten individuals at various ages ranging from children to the elderly. Chemotherapy is an effective method of dealing with cancer in children, but can cause anxiety. Anxiety felt by children causes them to be reluctant to return the treatment and undergo chemotherapy in the hospital. This study purpose to describe the anxiety level in cancer children before undergoing chemotherapy at the Bali Children’s Cancer Care Foundation House. This research was descriptive with cross-sectional design using consecutive sampling technique. This research sample was 30 children. These results of this study shows that 76,7% of children experienced severe levels of anxiety, 13,3% of children experienced moderate level off anxiety, and 10,0% of children experienced mild level of anxiety. Recommendations in this study are expected that parents always provide full support to minimize the level of anxiety felt by children.